Features of Language in President Jokowi’s Political Speech on Covid-19 Pandemic Handling in Indonesia - Maharsi, Eni (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
COVID-19 pandemic had forced state leaders to take various actions, one of which was through communicating the pandemic measures. In Indonesian context, the difficult times of the 2020-2021 COVID-19 pandemic had also challenged President Joko Widodo (Jokowi) to communicate his response to handling the pandemic differently from communication prior to the pandemic. Jokowi tried to gain compliance and support which could be identified from the linguistic features in his speeches of pandemic handling. This study discusses linguistic features in Jokowi's COVID-19 speech. Voyant-tool was used as a tool for identifying the most salient linguistic units. Analysis was carried out to determine patterns of lexical choices, to examine how these patterns helped construct the pandemic discursively. and to relate it to Jokowi's pandemic communication goals. Results reveal that first person singular I and first-person plural WE/ US were the most salient features. Second, the choice of structure and lexicon specifically indicated a strategy of inclusivity and the creation of a clear group identity. Inclusive WE functioned as linguistic strategy to build collective identity, sense of solidarity and unity of Indonesian, as well as indicating choice of acting as an interlocutor to equalize social actors. Exclusive WE/ US also emphasized identity, speaker involvement actions, personal pronoun I was persuasion device and marker of interpersonal relationship and positioning as the highest authority, while temporal deixis was employed to urge the sense of urgency.